VD_FINDINFO Décision / 2018 / 108 vom 9. Februar 2018 - VD Tribunal cantonal (2018)
DÉTENTION PROVISOIRE, PROLONGATION, RISQUE DE RÉCIDIVE | 221 al. 1 let. c CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)